Analysis of Leadership Failures, Crises, and Scandals in Various Sectors and Contexts in Argentina - Castro, Emilia (International Journal of Leadership and Governance, 2024)
Purpose: The aim of the study was to investigate the analysis of leadership failures, crises, and scandals in various sectors and contexts. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: An analysis of leadership failures, crises, and scandals in Argentina reveals recurring patterns across various sectors and contexts. Instances of corruption, mismanagement, and lack of accountability have plagued political, corporate, and social spheres. The failure to address systemic issues has exacerbated economic instability and social unrest, undermining trust in leadership. These challenges underscore the pressing need for comprehensive reforms and ethical leadership to foster sustainable development and restore public confidence. Unique Contribution to Theory, Practice and Policy: Transformational leadership theory, contingency theory & ethical leadership theory may be used to anchor future studies on the analysis of leadership failures, crises, and scandals in various sectors and contexts. Encourage practitioners to consider the perspectives of various stakeholders when analyzing leadership failures and developing strategies for crisis management and stakeholder engagement. Develop evidence-based policy recommendations aimed at preventing leadership failures and promoting effective leadership practices.